Wearout reliability studies of bonding wires used in nano electronic device packing - Gan Chong Leong (Institute of Nano Electronic Engineering, Universiti Malaysia Perlis, 2014)
The objective of this project is to evaluate the wearout reliability, apparent activation energy and Intermetallic compound (IMC) thickness growth of Au, Pd-coated Cu wire and Pd-doped Cu wire used in semiconductor packaging. Methodology of this work include investigation on the effects of bonding wires on wearout reliability of flash component, characterization of the apparent activation energy of IMC and HTSL test and formulation of the failure mechanisms in different wires.